From Transactions to Advocacy: The Role of Complaint Management and e-WOM in Shaping Referral Marketing in Indonesian E-Commerce - Cut Putri Herawati; Sugeng Lubar Prastowo; Wanda Yulia Utami (PT. Batari Edu Calya, 2026)
This study investigates the influence of customer value proposition (CVP), electronic word of mouth (e-WOM), and complaint management on purchase decisions in the Indonesian e-commerce sector, with referral marketing as a mediator and purchase satisfaction as a moderator. Using a quantitative cross-sectional survey, data were collected from 192 Tokopedia users via purposive sampling. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to test the research framework. The findings reveal that CVP, e-WOM, and complaint management significantly shape purchase decisions, while only e-WOM and complaint management exert direct effects on referral marketing. Conversely, purchase decisions and satisfaction do not significantly predict referral behaviors, underscoring that transactional outcomes alone are insufficient drivers of advocacy. These results advance consumer behavior theory by refining Expectation-Confirmation Theory and the Theory of Planned Behavior, highlighting the primacy of relational and experiential mechanisms such as complaint recovery and peer influence over transactional satisfaction. Practically, the study provides strategic guidance for e-commerce platforms in emerging markets, emphasizing the need to strengthen complaint management systems and leverage positive e-WOM to foster sustainable customer advocacy.